Transnational standard setting in accounting: Organizing expertise-based self-regulation in times of crises - Sebastian Botzem (Accounting, Auditing & Accountability Journal, 2014)
[Purpose:] The last four decades have seen the rise of the International Accounting Standards Board (IASB) as the core locus of transnational accounting regulation. Initial steps of associational cooperation were superseded by establishing a standard setting organization that heavily draws on consultation procedures. The purpose of this paper is to focus on recent changes in governance and accountability of IASB in the aftermath of the financial crisis. Emphasis is given to the organizational configuration, the ambivalence of consultation procedures and reactions to mounting criticism after the crisis. The paper proposes that IASB is the heart of a new transnational regulatory constellation in accounting. [Design/methodology/approach:] The material and analysis presented in the paper derives from an extensive review of official reports, consultation documents and related responses and a range of additional information available on IASB's web page. [Findings:] The paper analyzes how IASB uses legitimation strategies to defend its position as a transnational standard setter. From analysis of recent changes, the paper reveals a growing reliance on – and domination through – consultation procedures. The paper also shows the IASB'S swift action to counter substantial criticism emerging with the financial crisis. [Practical implications:] By highlighting developments surrounding IASB, its governance structure and the emphasis on consultation, the paper establishes the importance for public policy of further study and debate the operation of IASB. It could also contribute to re-politicize accounting regulation at the transnational level. [Originality/value:] IASB is an integral player in global financial governance processes and is only recently receiving substantial academic accounting research. This paper seeks to provide an introduction and critical account of the organization's development.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; legitimacy; financial crisis; due process; IASB; transnational regulatory constellation